2019
DOI: 10.21608/esj.2019.5477.1069
|View full text |Cite
|
Sign up to set email alerts
|

Povidone-Iodine 3.35% Solution versus Normal Saline for Irrigation in Lumbar Fusion Surgery: A Retrospective Study

Abstract: Background Data: Povidone-iodine is very effective broad spectrum antiseptic solution against different types of pathogens including methicillin-resistant Staphylococcus aureus and some strains of Enterococcus faecium based on the antiseptic properties of iodine. Purpose: To evaluate the effect of intraoperative 3.35 % povidone-iodine irrigation in lumbar spine fusion surgeries. Study Design: Retrospective clinical case study. Patients and Methods: 93 spine fusion surgeries in 2016 (Group I) and 112 fusion sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Moreover, they did not find any linear correlation between PVI soaking time and the fusion rate. 13 We found almost similar results with higher doses of PVI; however, the infection rate did not decrease to zero in the current experiment. In addition to wound irrigation, several patients, wounds, and environmental strategies are needed to prevent intra-operative wound contamination, 5 which explains the dissimilarity of infection rates.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, they did not find any linear correlation between PVI soaking time and the fusion rate. 13 We found almost similar results with higher doses of PVI; however, the infection rate did not decrease to zero in the current experiment. In addition to wound irrigation, several patients, wounds, and environmental strategies are needed to prevent intra-operative wound contamination, 5 which explains the dissimilarity of infection rates.…”
Section: Discussionsupporting
confidence: 80%
“…Recent clinical studies have shown that wound irrigation with PVI significantly reduces the infection rate in spinal surgeries without causing any serious side effects. 12,13,20,21 While there is no consensus on the safe dose and irrigation time with PVI. J Strohecker et al found that intra-lumbar disc surgery lavage of diluted PVI decreases the infection rate by 1.6%; however, the concentration of PVI was not provided.…”
Section: Discussionmentioning
confidence: 99%
“…2950 relevant papers were looked at, and 29 studies published between 2006 and 2023 met the criteria to be included in the meta‐analysis 13,14,24–50 …”
Section: Resultsmentioning
confidence: 99%
“…For the current meta‐analysis, 29 examinations from 2006 to 2023 were included; of these, 11 181 people had instrumented SS of them 4421 were using vancomycin as intrawound management, 908 were using povidone‐iodine, and 5852 were using control. The sample size was 41–1822 people 13,14,24–50 . The data that was looked at showed that using vancomycin and povidone‐iodine as intrawound management had a much lower deep SSI than using a control group of instrumented SS subjects.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited data on the safety dose spectrum of PVI for spinal surgeries. [12][13][14] On the other hand, normal saline has the lowest toxicity, but it only dilutes and does not cleanse the contaminants. 13 We conducted the current randomized clinical trial aimed to evaluate the effect of wound irrigation with PVI and normal saline on infection rate, wound healing, fusion status and clinical outcomes of spinal surgery.…”
Section: Introductionmentioning
confidence: 99%